The Commercial Profitability of Growing Hybrid Eucalyptus Clones in The Coast Province, Kenya - Balozi Bekuta Kirongo; Kingiri Senelwa; Kimani G K; Imo Moses; Onkware Augustino; Lazane Etiégni (Jurnal Manajemen Hutan Tropika, 2014)
Due to the current high demand for timber, fuelwood, and building poles and the realization that tree growing may pay dividends in the short and long term, many farmers are planting trees on their farms. Farmers are increasingly planting eucalyptus partly due to the fast growth rates of the hybrid clones as well as the opportunity to earn money within a short time. In this paper we report on the profitability of growing eucalyptus hybrid clones in the coastal region, Kenya. Tree growth and cost data was sourced from farmers in Malindi, Kilifi, and Msambweni. Market information was sourced from hardwares in North and South Coast while tree growth models were used to provide average tree sizes at various ages. Results showed that a farmer could make a net income of upto Kshs.500,000.00 (USD6,250) in 5 years. Farmers in the South Coast (Kwale and Msambweni) spent more on transport than their counterparts in the North Coast (near Gede-KEFRI). This, added to the fact that trees in the South Coast (Msambweni) grew less compared to those in North Coast meant that farmers in the south made less profits.